MiR‐34c‐5p modulates X‐box–binding protein 1 (XBP1) expression during the adaptive phase of the unfolded protein response. Issue 10 (17th July 2019) - Bartoszewska, Sylwia; Cabaj, Aleksandra; Dąbrowski, Michał; Collawn, James F.; Bartoszewski, Rafal
ABSTRACT: During endoplasmic reticulum (ER) stress conditions, an adaptive signaling network termed the unfolded protein response (UPR) is activated. The UPR's function is to increase ER protein‐folding capacity in order to attenuate ER stress, restore ER homeostasis, and, most importantly, promote cell survival. X‐box–binding protein 1 (XBP1) is one component of the UPR and is a proadaptive transcription factor that is subject to transcriptional, post‐transcriptional, and post‐translational control. In the present study, we identified a post‐transcriptional mechanism mediated by miR‐34c‐5p that governs the expression of both the spliced (active) and unspliced (latent) forms of XBP1 mRNAs. We showed that miR‐34c‐5p directly attenuates spliced XBP1 ( XBP1s ) mRNA levels during ER stress and thus regulates the proadaptive component of the UPR that is mediated by XBP1s without interfering with the induction of apoptotic responses.—Bartoszewska, S., Cabaj, A., Dabrowski, M., Collawn, J. F., Bartoszewski, R. miR‐34c‐5p modulates X‐box‐binding protein 1 (XBP1) expression during the adaptive phase of the unfolded protein response. FASEB J. 33, 11541–11554 (2019). www.fasebj.org